2021
DOI: 10.21272/mmi.2021.2-20
|View full text |Cite
|
Sign up to set email alerts
|

Consumer behavior in digital era: impact of COVID 19

Abstract: The main goal of this paper is to research differences that start to change consumer behavior in the digital era since the advent of COVID 19. The events associated with the pandemic that led to increased social distance and complete lockdown undoubtedly affect not only the economic situation territories and countries in general, but also on the behavior of each individual. The situation that has arisen has forced more and more consumers to meet their needs with the help of digital tools, and this process has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…Behavioral economics is at the peak of research. Many works (Alefan, 2022;Arora, 2019;Ata, 2021;Biewendt, 2021;Bildiren, A., 2022;Chong, 2012;Davidaviciene, 2019;Dittmar, 2014;Dunska, 2018;Fernandes, 2014;Kim, 2008;Kim, 2011;McKnight, 2001;Napoli, 2014;Prothero, 2011;Rahmanov, 2021;Salé, 2021;Wong, 2003) is devoted to the study, systematization, evaluation, modeling of behavioral factors. A significant number of publications are devoted to the study of fundamental and practical approaches to the systematization of scientific knowledge based on the use of bibliometric analysis, in particular (Dubina, 2020;Duffy, 2020;Kolosok, 2021;Letunovska, 2021;Makerska, 2021;Zolkover, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Behavioral economics is at the peak of research. Many works (Alefan, 2022;Arora, 2019;Ata, 2021;Biewendt, 2021;Bildiren, A., 2022;Chong, 2012;Davidaviciene, 2019;Dittmar, 2014;Dunska, 2018;Fernandes, 2014;Kim, 2008;Kim, 2011;McKnight, 2001;Napoli, 2014;Prothero, 2011;Rahmanov, 2021;Salé, 2021;Wong, 2003) is devoted to the study, systematization, evaluation, modeling of behavioral factors. A significant number of publications are devoted to the study of fundamental and practical approaches to the systematization of scientific knowledge based on the use of bibliometric analysis, in particular (Dubina, 2020;Duffy, 2020;Kolosok, 2021;Letunovska, 2021;Makerska, 2021;Zolkover, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the paper Bilan et al [37] justified their hypothesis about how the amount of financial resources attracted through digital platforms is dependent on the quantitative characteristics of the relevant determinants. The digitalization of marketing policy includes many approaches and methods: strategic communication with influencers [38,39], the aspect of branches [40][41][42], SMM marketing [43][44][45], and behavioral aspects [46,47]. In the article Kim et al [48] demonstrated through bibliometric studies that digital marketing is leading the way in offering new methods to reach, promote, involve, supply, and propose goods and services to customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Higher expenses of doing business, product interruptions, disruptions in both personal and professional travel, non-trade measures, and a heightened degree of uncertainty [12] caused by the COVID-19 epidemic amid the economic crisis had a significant influence on global commerce. Covid-19 has had a significant influence on the business community in Sub-Saharan Africa, and as a result, digital marketing has become increasingly important as a channel through which companies may sell their wares.…”
Section: Introductionmentioning
confidence: 99%